Emerging Pharmacological Interventions for Chronic Venous Insufficiency: A Comprehensive Systematic Review and Meta-Analysis of Efficacy, Safety, and Therapeutic Advances - Camila Botelho Miguel; Ranielly de Souza Andrade; Laise Mazurek; Melissa Carvalho Martins-de-Abreu; Jamil Miguel-Neto; Aurélio de Melo Barbosa; Glicélia Pereira Silva; Aristóteles Góes-Neto; Siomar de Castro Soares; Javier Emilio Lazo-Chica; Wellington Francisco Rodrigues (Pharmaceutics)
Background/Objectives: Chronic Venous Insufficiency (CVI) is a progressive vascular condition characterized by venous hypertension and chronic inflammation, leading to significant clinical and socioeconomic impacts. This study aimed to evaluate the efficacy and safety of emerging pharmacological interventions for CVI, focusing on clinical outcomes such as pain, edema, cutaneous blood flow, and quality of life. Methods: Eligible interventions comprised new vasoprotective drugs, such as hydroxyethylrutoside, Pycnogenol, aminaphthone, coumarin + troxerutin, and Venoruton, compared to the standard therapy of diosmin and hesperidin. Results: Hydroxyethylrutoside and Pycnogenol showed significant benefits in pain reduction and resting flux improvement, with mean differences of 38 (95% CI: 10.56–65.44) and 25.30 (95% CI: 18.73–31.87), respectively. Improvements in edema and quality of life were less consistent. Substantial heterogeneity was observed (I2 = 100%, p < 0.001). Conclusions: Hydroxyethylrutoside and Pycnogenol emerge as promising alternatives for managing CVI. However, limitations such as high heterogeneity, small sample sizes, and methodological inconsistencies highlight the need for more robust and standardized clinical trials. This study underscores the importance of personalized and cost-effective strategies, particularly in resource-limited settings.